Freight Transport Emissions Calculators as a Tool of Sustainable Logistic Planning - Jan Chocholac; Jaroslava Hyrslova; Tomas Kucera; Stanislav Machalik; Roman Hruska (Communications - Scientific letters of the University of Zilina, 2019)
The freight transport performance is growing. The transport sector is also one of the largest producers of emissions. This must be reflected not only by production companies but also by other stakeholders. The issue of transport emissions is particularly important for city residents, so today the concept of sustainable city logistics is emphasized. Companies should deal with the amount of produced emissions. The use of emission calculators would support operational, tactical and strategic business decision-making. The aim of this article is to analyse the approaches used in available free calculators of emission arising from the freight transport. The focus was on the transport modes that calculators include, input data, output data and methodologies used to calculate emissions. The method of systematic review was used to search analysed freight transport emissions calculators. The method of content analysis was used to analyse inputs, outputs and freight transport emissions calculator’s methodologies. The method of qualitative comparative analysis was used to analyse and compare the freight transport emissions calculators.